Cooperation of Fe(II) and peroxymonosulfate for enhancement of sulfamethoxazole photodegradation: mechanism study and toxicity elimination. Issue 59 (28th September 2020) - Gong, Han; Chu, Wei; Gong, He; Huang, Airu; Lin, Jingjun; Yan, Muting
Abstract : For the first time, this study systematically revealed the potential, the mechanism and the risk of removing sulfamethoxazole by UV/Fe(II)/peroxymonosulfate. Abstract : This study aims at systematically examining the potential of removing the emerging pollutant sulfamethoxazole (SMX) from aqueous solution under photo-assisted peroxymonosulfate (PMS) activation by Fe(ii ). The residual SMX was determined by HPLC analysis. The concentration of Fe(ii ) ([Fe(ii )]) was monitored during SMX degradation. Fe(ii ) and PMS cooperated with each other for faster SMX photodegradation; a relatively lower or higher molar ratio between Fe(ii ) and PMS led to lower SMX removal efficiency due to the insufficient radicals or scavenging effect. A fixed reaction ratio of [Fe(ii )]Δ  : [PMS]0 with 1.6 : 1 at the first 5 min was detected for reactions with [Fe(ii )]0 ≥ 0.5 mM or [PMS]0 ≤ 0.25 mM. The pH level of around 6.0 was recommended for optimal SMX removal under the treatment process UVA + Fe(ii ) + PMS. Six transformation products were detected through UPLC/ESI-MS analysis, and four of the proposed intermediates were newly reported. Concentrations of the intermediates were proposed based on the isoxazole-ring balance and the Beer–Lambert law. Total Organic Carbon (TOC) reduction was mainly attributed to the loss of benzene ring, N–S cleavage, and isoxazole ring opening during SMX degradation. The contributions of reactive species OH˙ and SO4 ˙ − were determined based on quench tests. The acute toxicity of SMX to the rotifers was eliminated after the proposed treatment, demonstrating that the process was effective for SMX treatment and safe to the environment.